2007
DOI: 10.1080/08860220601039098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-HCV Positivity on Markers of Malnutrition and Inflammation in Hemodialysis Patients

Abstract: Aim. To investigate the influence of anti-HCV positivity on markers of malnutrition and inflammation in hemodialysis (HD) patients. Methods. Stable HD patients who had persistently negative or positive HCV antibodies (at least three) and without elevated aminotransferase levels in routine periodical tests with a duration of more than 12 months were included. Patients with conditions known to be associated with acute-phase responses or clinically active (HCV RNA positive) or advanced liver failure were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Iancu et al determined that 77.5% HD patients were anti-HCV reagents but only 12.19% had elevated CRP levels [4] . Zumrudtal et al, comparing anti-HCV (+) with anti-HCV (-) individuals, regarding some acute inflammatory markers, verified that these parameters were not different between the groups [5] . On the other hand, it was shown that HCV (+) patients have more severe signs of malnutrition-inflammation complex syndrome than HCV non-reagent individuals [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Iancu et al determined that 77.5% HD patients were anti-HCV reagents but only 12.19% had elevated CRP levels [4] . Zumrudtal et al, comparing anti-HCV (+) with anti-HCV (-) individuals, regarding some acute inflammatory markers, verified that these parameters were not different between the groups [5] . On the other hand, it was shown that HCV (+) patients have more severe signs of malnutrition-inflammation complex syndrome than HCV non-reagent individuals [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that HCV infection is associated with increased expression of interleukin-6 [23–26], while others have not observed increased expression [27,28]. One study indicated that the interleukin-6 response to stimulation of toll like receptors 3 and 4 is compromised in HCV infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is not at all surprising that they did not find any differences in markers of inflammations and nutritional status in their study. This is because they had excluded patients with active disease (positive for HCV RNA) and advanced liver disease.…”
Section: Vui Heng Chongmentioning
confidence: 95%